(untitled) (El Taco en la Brea, 2022)
Social democracy in Western Europe was due to a series of historical and political conditions which were not to be found in Latin America in the twenties. On the other hand, the liberal policies applied in the region have produced a marked heterogeneity of the labour force and a deepening of social inequalities which make the prospects more complicated. Garcia Mellid created CIPA in 1938 as a rejection of any essentialist definition of Americanism: CIPA was a referential point to solve some of the dilemmas aroused by the aesthetic avant-garde